(untitled) (Research, Society and Development, 2024)
Neonatal sepsis is a systemic response to infection in the first month of a newborn’s life. This condition can be classified as early, when it occurs before 72 hours of life; and late, after this period. Objective: To describe clinical data and risk factors of neonatal sepsis in a referral hospital in Paraná, Brazil. Methodology: Retrospective, descriptive-exploratory study, with quantitative analysis of medical records of newborns with sepsis admitted to the NICU, between 2020 and 2023. The collection was performed using a checklist, and analysis used the SPSS software (25.0) to describe frequencies. The research was approved by the Ethics Committee of Universidade Paranaense (Protocol 1.993.257). Results: Between 2020 and 2023, 895 medical records of newborns were analyzed and, of these, 490 (54.7%) developed sepsis. The majority were male (53.5%), born by surgical delivery (71.4%), admitted between 0 and 7 days of life (97.3%), with a stay of more than 15 days in the NICU. The Apgar score was ≥ 7 in 71.1% at the 1st minute and 89.5% at the 5th minute. Respiratory problems were the main cause of hospitalization (84.2%), and 68.2% of the sample presented early sepsis. In the treatment, 98.4% of the neonates used SOG and 85.9% used PICC, in addition, DVA was used in 78.6% of the cases, with Gentamicin (86.5%) and Ampicillin (86.1%) being the most used antibiotics. Conclusion: The research highlights the importance of continuous monitoring, suggesting further studies to improve the prevention and treatment of neonatal sepsis.